Family management risk and protective factors for adolescent substance use in South Africa - Beatrice Wamuyu Muchiri; Monika M. L. dos Santos (BMC, 2018)
Abstract Background An increasingly recognised prevention approach for substance use entails a reduction in risk factors, and the enhancement of promotive, or protective factors in individuals and the environment surrounding them during their growth and development. Methods This exploratory study evaluated the effect of potential risk and protective factors associated with family management relating to adolescent substance use in South Africa. Exploratory analysis and cumulative odds ordinal logistic regression modelling was performed on the data, while controlling for the influence of demographic and socio-economic characteristics on adolescent substance use. Results The most frequently used substances were cannabis, followed by other illicit substances and alcohol in decreasing order of use intensity. The specific protective, or risk effect of family management factors, varied according to substance. Risk factors associated with demographic and socio-economic factors included being male, of a younger age, lower education grades, of a coloured ethnicity, adolescents from divorced parents, and unemployed or fully employed mothers. Several family management factors, categorised as parental monitoring, discipline, behavioural control and rewards, demonstrated either risk or protective effects on adolescent substance use. Conclusions This exploratory study demonstrated that various risk and protective factors associated with family management may affect adolescent substance use. Interaction amongst risk or protective factors, as well as the type of substance, should be considered when further considering interventions based on these risk or protective factors.